A Silicon-Based D-Band Miniaturized Diplexer Using Perturbed Dual-Mode Junction-Cavity - Zhang, Zi-Qi; Zhou, Liang; Zhang, Cheng-Rui; Zhou, Kang (IEEE transactions on microwave theory and techniques, 2025)
A D-band silicon-based diplexer is proposed using metallized rectangular waveguide cavities (MRWCs). Perturbed dual-mode junction-cavity is achieved as the connection network to form the lower and upper channels. The synthesized, simulated, and measured S-parameters of the diplexer show a good agreement. The measured insertion loss is 1.77 dB with a bandwidth of 2.5% at 144.1 GHz and 1.38 dB with a bandwidth of 3% at 153.9 GHz. The return loss (RL) is better than 10 dB, and the adjacent channel rejection is better than 27 dB. The measured center frequency (CF) shifts by 0.05% and 0.5%, with bandwidth variations of 7% and 11%, compared to simulation in the lower and upper channels, respectively. The overall size of the diplexer is only 1.5× 1.62 mm2. It demonstrates an excellent performance in terms of low loss and compact size compared to state-of-the-art works using our metallized through silicon ring trench manufacturing (MTSRTM) technology. The proposed silicon-based diplexer can be further integrated directly with transceivers in radar or communication systems at D-band.